2013
DOI: 10.1063/1.4816515
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of hydrogen on the surface and sub-surface of Cu(111)

Abstract: Articles you may be interested in 1,2-Dibromoethane on Cu(100): Bonding structure and transformation to C2H4 J. Chem. Phys. 135, 064706 (2011) The interaction of atomic hydrogen with the Cu(111) surface was studied by a combined experimental-theoretical approach, using infrared reflection absorption spectroscopy, temperature programmed desorption, and density functional theory (DFT). Adsorption of atomic hydrogen at 160 K is characterized by an anti-absorption mode at 754 cm −1 and a broadband absorption in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
11
33
0
Order By: Relevance
“…8. The obtained adsorption energies for both the adsorption of single H-atoms [23,[47][48][49] and for the formation of 1 ML at Cu(100) [49] are in good agreement with literature data. For 1 ML at Cu(100), as previously reported by other authors [49], we also found that the shifted fourfold hollow geometry is more stable than the centered fourfold hollow.…”
Section: Segregation Of H-atoms At the R3 R5 And R11 Gbssupporting
confidence: 88%
“…8. The obtained adsorption energies for both the adsorption of single H-atoms [23,[47][48][49] and for the formation of 1 ML at Cu(100) [49] are in good agreement with literature data. For 1 ML at Cu(100), as previously reported by other authors [49], we also found that the shifted fourfold hollow geometry is more stable than the centered fourfold hollow.…”
Section: Segregation Of H-atoms At the R3 R5 And R11 Gbssupporting
confidence: 88%
“…The spectrum (c) is characteristic of co-adsorbed CO and H, as it shows that the presence of H suppresses the adsorption of CO. 28 The spectrum obtained after similar preparation using flat Cu(111) shows a slightly red shifted peaks at 1132 and 2059 cm À1 for adsorbed H and CO, respectively, as reported previously. 28 Annealing of the system in (c) to 200 K results in the complete desorption of CO and the disappearance of the surface Cu-H vibration peak as shown in spectrum (d) due to the migration of H to sub-surface sites, leading to the formation of a thin copper hydride (CuH) layer as described earlier on Cu(111) surfaces. 28 Spectrum (e) was obtained after re-cooling to 100 K and re-adsorption of CO on top of the CuH surface.…”
Section: Resultssupporting
confidence: 78%
“…Subsurface hydrogen absorption, well known for Pd(110) [33][34][35][36][37], Pd(111) [38][39][40], Pd(100) [41,42], and Pd(311) [43], has been also reported for Ru(0001) [44], Cu(111) [45] and Ni(111) [46]. The diffusion of atomic hydrogen into the subsurface of smooth, but not on defected, Pt(111) surfaces has been suggested experimentally [23,47] and theoretically [48,49].…”
Section: Introductionmentioning
confidence: 94%